2016
DOI: 10.1590/0100-3984.2014.0048
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector computed tomography angiography of the renal arteries: normal anatomy and its variations

Abstract: Conventional angiography is still considered the gold standard for the study of the anatomy and of vascular diseases of the abdomen. However, the advent of multidetector computed tomography and techniques of digital image reconstruction has provided an alternative means of performing angiography, without the risks inherent to invasive angiographic examinations. Therefore, within the field of radiology, there is an ever-increasing demand for deeper knowledge of the anatomy of the regional vasculature and its va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0
17

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 21 publications
1
8
0
17
Order By: Relevance
“…It is essential for the radiologists and surgeons to have background knowledge of normal range of renal artery measurements and variation in measurementsin a specific population as this can affect complex and expertise required procedure. 23 , 24 In our study a significant difference was observed between mean diameter of right and left main renal arteries. Mean diameter of right renal artery was found to be smaller than mean diameter of left renal artery.…”
Section: Discussionsupporting
confidence: 51%
“…It is essential for the radiologists and surgeons to have background knowledge of normal range of renal artery measurements and variation in measurementsin a specific population as this can affect complex and expertise required procedure. 23 , 24 In our study a significant difference was observed between mean diameter of right and left main renal arteries. Mean diameter of right renal artery was found to be smaller than mean diameter of left renal artery.…”
Section: Discussionsupporting
confidence: 51%
“…Finally, Mello Júnior et al ( 2 ) provided practical recommendations for the interpretation of CT angiography of the renal arteries, guiding the detailed description, plus measures, which promotes greater consistency in communicating the findings to the surgeon, as previously suggested by other authors ( 15 ) .…”
mentioning
confidence: 95%
“…In his Traité d'Anatomie Humaine , the classical anatomist Testut noted that "the kidneys, as well as other organs that perform important functions, have an extremely rich and complex vasculature" ( 1 ) . In the previous issue of Radiologia Brasileira , Mello Júnior et al ( 2 ) described the normal appearance of the renal arteries and their most common anatomical variations, as observed with computed tomography (CT) angiography. The authors also discussed the technical aspects of implementing CT angiography, the post-processing of images, and the terminology involved, as well as the clinical and surgical implications.…”
mentioning
confidence: 99%
See 2 more Smart Citations